Government Project Initiation and its Influencing Factors - An Empirical Research - C S, Gopalakrishnan; K K, Sanitha; Adaikalam J, John (International Journal of Psychosocial Rehabilitation, 2020)
Infrastructure is the underlying material structure of an economy to boost the socio-economic activity in general. It is the fundamental requirement for the socio-economic development of a society. The welfare of the society can be augmented only through the presence of adequate infrastructure facilities. These include the transport, communication, water supply, irrigation, warehousing and other basic systems. Roads, Bridges, Dams, Canals, Pipelines, Railways, Airports and Harbours are the integral part of infrastructure. It is the responsibility of the Government to create and maintain the infrastructure facilities for promoting the growth of the economy. Government is usually evaluated through the success of the projects since they are formulated and implemented. The responsible governments try to find out the urgent and burning needs of the people in various walks of life. They have to give much attention in the sectors of education, healthcare, social security, law and order and other fields of socioeconomic development. This study is mainly focused to identify and analyze the factors that influence the Government Project initiation. The sample unit is the Users of Government Projects, and the sample size is 420.